If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 0 = 12(3c + 4) Reorder the terms: 0 = 12(4 + 3c) 0 = (4 * 12 + 3c * 12) 0 = (48 + 36c) Solving 0 = 48 + 36c Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-36c' to each side of the equation. 0 + -36c = 48 + 36c + -36c Remove the zero: -36c = 48 + 36c + -36c Combine like terms: 36c + -36c = 0 -36c = 48 + 0 -36c = 48 Divide each side by '-36'. c = -1.333333333 Simplifying c = -1.333333333
| 4-7/2x=25 | | =3a^2+14a^2 | | -5(3-2)=z+1 | | -27=2w+3(w-4) | | 9+3p-5t+3= | | 31-7r=-6r-4(1-r) | | -5-2/7x=-1 | | -5-2/7x=25 | | 2(x+3)+5x=12 | | -90=5(2n-8) | | t/-6-8=7 | | 4+1/3y=-5 | | -3/2x-9=6 | | u/9=1 | | 5x/8=2x/3-1 | | 5x+13=9x-39 | | -7p+3p=8 | | 3lnx=2 | | 7z-8=3z+24 | | -2/5x-1=3 | | 777/6 | | -4(x+5)=3(x-11) | | 2x-0.3-2.6x=3.42 | | 2x*5=11 | | v+5=8 | | 8=-5/6z-12 | | 2-3(3x-4)+5=52 | | -3(x+8)-2(4x-3)=-7 | | -3=5v-5 | | Xlnx=6lnx | | x+3.5=9 | | (4f+5)-(-5f-40)=180 |